Leveraging technology-speaking tasks to promote Indonesian EFL students' communicative performance - Oktavia Widiastuti; Teguh Sulistyo; Saiful Marhaban (Universitas Syiah Kuala, 2026)
This study investigates the effects of technology-enhanced speaking tasks on the communicative performance of intermediate-level Indonesian EFL students. Inspired by González-Lloret and Ortega’s (2014) framework on technology-mediated tasks, technology-enhanced speaking tasks were created and applied across YouTube video-making tasks. Participants in this study were 40 students of English majors enrolled in a speaking course. They were recruited for a mixed-method study combining pre-experimental and survey designs. The video task analytics, as well as the pretest and posttest scores, provided quantitative data. The students’ questionnaires and interviews, which explored their perceptions of using technology-enhanced speaking tasks, constituted the qualitative data. The findings showed that when teachers employed technology to support learning, students’ communicative performance, as well as their ability to use English in face-to-face, online, and real-world interactions, increased significantly, covering fluency, accuracy, and complexity. According to student experiences, communicative performance and self-efficacy are motivational factors that, when fostered in an online classroom environment, inspire students to try out language creatively. They enhanced their digital literacy and collaborative learning opportunities, thereby increasing confidence in spontaneous speech production and reducing anxiety when engaging in oral communication tasks. The use of digital video-based activities promotes sustainable educational innovation by enhancing students’ communicative competence, digital literacy, and readiness for real-world communication.